Political economy of wheat value chains in post-revolution Sudan - Resnick, Danielle (International Food Policy Research Institute, 2021)
Wheat flour and bread have played a central role in Sudan’s political economy throughout the country’s post-independence history. In 2019, increasing bread prices precipitated the protests that ousted the government of Omar al-Bashir. How has Sudan’s recent political transition and economic circumstances impacted distortions within the wheat value chain? What are the preferences of relevant stakeholders for improving the affordability of wheat products and the productivity of domestic wheat farmers? This paper addresses these questions by drawing on key informant interviews in Sudan and utilizing a political settlements approach, which captures the underlying distribution of power among elites and citizens. The post-revolution political settlement contains a much broader distribution of power shared between a civilian alliance movement and the military, each of which has distinct interests in the wheat value chain. The paper elucidates the preferences of different stakeholders to address distortions and discusses bottlenecks that need to be overcome for those options to be feasible. In doing so, the analysis reveals that, while the of subsidizing bread remains contentious, there are broader coalitions for interventions related to regulatory and monitoring reforms, improvements in domestic wheat procurement, enhanced agricultural investments, and targeted cash transfers to cushion subsidy reductions.